Empathy in the doctor-patient relationship - Baptista, Sofia (2012)
The clinical interview is a key element in the construction of the doctor patient relationship. It can influence adherence to therapy. Ethical issues in the doctor-patient relationship, verbal and non-verbal communication, and errors to avoid in clinical communication have been widely discussed. However, despite agreement regarding its importance, the concept of physician empathy is rarely explored and may be misinterpreted or cause confusion